(untitled) (Al-Mansour Journal, 2022)
Countries depend on different resources to build up their economies. Some depend on what they mine such as oil, gold, and diamond ……..etc. Others depend on trade and ports, and some others depend on tourism, summer vacations, trade, agriculture or a mixture of what has been mentioned above. Yet many countries do not have the wealth or the resources to build up their economies. So, they tend to unearth new resources which bring about wealth. The information has it that if distancing the resource is well invested and supported by the right structure, there will be national wealth that brings about large revenue. Many countries especially in the Arab world, seek to recognize the perception already, in order to mentioned find and establish strong and proper structure for informational economy and to overcome the obstacles and challenges that face it. The study aims at defining the supporting structures to identify information features and then to examine the experiment of the economies, of the developing countries. One result of the study is that great challenges: scientific, technical, cultural, social and financial materializes, on the ground of the poor information followed. One of the recommendations is the necessity to address our selves toward informational economy, after finding out solutions for the problems and also finding the infrastructures and superstructures of information that can be achieved through various plans